Towards responsible lending in Namibian consumer credit law : a comparative investigation - Asheela, Ndatega Victoria (University of Pretoria, 2017)
The regulation of consumer credit in Namibia mainly is provided for by the Usury Act 73 of 1968 and the Credit Agreements Act 75 of 1980. These legislative enactments originated in South Africa and were applied in South West Africa during the period of South Africa’s mandate over what is now the Republic of Namibia. Despite the fact that these enactments are over 35 years old, they are substantially unchanged. In response to an awareness of the threat of consumer over-indebtedness and other events such as financial crises, the purpose in this thesis is to undertake a situational analysis of the debt prevention measures as provided for by the Namibian legislative framework and the extent of protection these measures afford consumers in terms of irresponsible credit and over-indebtedness. A broad survey of the policies aimed at promoting responsible lending benchmarks the Namibian consumer credit regulatory framework against the leading international best principles which have been developed in response to global economic challenges. The Namibia Financial Institutions Supervisory Authority in the 2014 Microlending Bill proposes to introduce responsible lending practices in the form of a compulsory pre-agreement assessment of the prospective consumer before providing them with credit. In a comparative investigation, the creditworthiness assessment and related measures central to the responsible lending regimes in South Africa and Australia are considered. Measuring the Namibian consumer credit regulatory framework against these recent developments, it is submitted that the current debt prevention measures are inadequate in protecting consumers from irresponsible credit lending and the risk of consumer over-indebtedness. This thesis supplies reasons for the need in Namibia to update the regulatory structure of the credit industry in order to protect consumers. As a contribution to the promotion of a culture of responsible lending in the Namibian consumer credit market, the thesis proposes the introduction of responsible lending measures in Namibia’s consumer credit legislative framework.
Keywords: Consumer credit; Debt; Namibia